A study on the factors that influence the sales competencies of employees in international sales division at GITN Sdn. Berhad / Amirul Asraf Wahin and Amirrul Zunnurain Azimi - Wahin, Amirul Asraf; Azimi, Amirrul Zunnurain (Faculty of Business and Management, 2015)
Sales force or team from all types of industry nowadays are lacking on the ability to become more persuasive and the ability to generate maximum profit from the product or services that their company offers. Competencies played a major role in finding and creating the abilities and capabilities that every sales person or any types of employee to help them to grow, become efficient and survive in the working world. Hence, this study focuses on the factors that influence the sales competencies with the international sales division at GITN Sdn. Berhad such as adaptability and innovation, customer services, optimistic and communication skills. A survey was carried out at Level 31, Menara TM, Jalan Pantai Baru at Bangsar. 120 respondents were managed to be identify out as the sample size from the 300 population. Multiple regression analysis was used to test the model and hypotheses. The survey result indicates that adaptability and innovation, customer services and optimistic are supported. In the other hand, communication skills are not supported.